Masjid Pathok Negoro Mlangi: Respon Masyarakat Mlangi Terhadap Renovasi Masjid Pada Tahun 2012 - Umi Azizah (UIN Sumatera Utara Medan, 2017)
The mosque is a place of worship of muslim, one of them is to perform the congregational prayers. Mosque Pathok Negoro Mlangi besides being use as a place of prayers congregation is also used as a place of spreading of Islam religion in Mlangi. The status of Mosque Pathok Negoro Mlangi is under the rule of Sultanate Yogyakarta. This mosque is also used as a cultural heritage and classified into cultural heritage buildings protected by UU No 11 in 2010. So, it is not arbitrary people can change the shape of the building. This study aims to determine the response of Mlangi community to renovate Mosque Pathok Negoro Mlangi in 2012. Data collection is done by interview, observation, and documentation, as well as verivication and interpretation to know the source validity. The community’s response to the renovation of the mosque in 2012 contradicts each other. Some people who support but not a few who refuse the renovation. The motive for the renovation in 2012 is to restore the characteristics of the mosque building Pathok Negoro Mlangi at the mosque Kagungan Dalem which has been lost due to renovations made in 1985 by Mlangi community.Key Word: Mosque Pathok Negoro Mlangi, Society Mlangi, Renovation Masjid merupakan tempat beribadah umat Islam, salah satunya untuk menjalankan sholat berjamaah. Masjid Pathok Negoro Mlangi selain digunakan sebagai tempat sholat berjamaah, juga digunakan sebagai pusat penyebaran agama Islam di Mlangi. Status Masjid Pathok Negoro Mlangi berada di bawah naungan Kesultanan Yogyakarta. Masjid ini juga dijadikan sebagai warisan budaya dan digolongkan kedalam bangunan cagar budaya yang dilindungi dengan UU No 11 Tahun 2010. Sehingga tidak sembarangan orang bisa mengubah bentuk bangunan tersebut. Penelitian ini bertujuan untuk mengetahui respon masyarakat Mlangi terhadap renovasi Masjid Pathok Negoro Mlangi pada tahun 2012. Pengumpulan data dilakukan dengan wawancara, observasi, dan dokumentasi serta melakukan verifikasi dan interpretasi untuk mengetahui keabsahan sumber. Respon masyarakat Mlangi terhadap renovasi masjid yang dilakukan pada tahun 2012 saling bertentangan. Sebagian masyarakat banyak yang mendukung dan ada juga yang menolak renovasi dilakukan. Motif dilakukannya renovasi pada tahun 2012 adalah, untuk mengembalikan ciri khas bangunan Masjid Pathok Negoro Mlangi sebagai masjid Kagungan Dalem yang telah hilang akibat renovasi yang dilakukan pada tahun 1985 oleh masyarakat Mlangi.Kata kunci: Masjid Pathok Negoro, Masyarakat Mlangi, Renovasi